117k views
2 votes
If f(x) = - x + 4 and g(x) = x ^ 2 - 5 , then f(g(-2))=?

User Thomas BP
by
4.0k points

1 Answer

4 votes

Answer:

Explanation:

using your f(x) I want to show you how to plug in different things itnot he function.

f(x) = -x + 4

f(1) = -1 + 4 = 3

f(2) = -2 + 4 = 2

f(m) = -m + 4

f(abc) = -(abc) + 4

f(h(x)) = -h(x) + 4

Does that help? what if you replaced h(x) with g(x)? Of course you already have that x so you could make it a little simpler as well. Let me know if you don't quite get it.

User Ujwal Manjunath
by
5.1k points